Serum Uric Acid as a Marker of Coronary Artery Disease in Type 2 Diabetes Mellitus Patients: An Observational Study - Nupur Shah (Journal of Clinical and Preventive Cardiology)
Background: Cardiovascular disease is the most prevalent cause of morbidity and mortality in diabetic patients. Hypertension, obesity, and smoking are well-established risk factors for coronary artery disease (CAD) in diabetes. Hyperuricemia is an emerging risk factor for insulin resistance and cardiovascular disease. Our objective in the present study was to assess the association of serum uric acid with cardiovascular disease and its risk factors in type 2 diabetes mellitus.